SISTEM PENJUALAN KREDIT DENGAN DUA HARGA DALAM TINJAUAN SYARIAH - Wijayanti, Anita; Hendrik, Hendrik (Manajemen Bisnis Syariah, 2012)
The emergence of two credits in the sale price of a problem that is often discussed in the rules of Islamic economics, because excess debt service stated in the flower, while the legal interest is haram, so there is a problem How does the law of two prices in the sale of credit in terms of Al Quran and Al Hadith ?                 The scholars disagree since to the present so as to produce three opinions, namely (1) That is an absolute falsehood bai´atain is (according to Ibn Hazm), (2) That the bai´atain is forbidden, except when the two prices (sell) it set (split) at one price only (ie the price of credit or cash price only), and (3) that the bai´atain is haram, but if it has occurred and the transaction price (selling) the lower set, then this is permitted (permissible).                 Based on his interpretation, the interpretation of the more shohih sahabatlah (right), rojih (strong), and precedence, they assert that the main core of the election ban bai´atain is offering two types of the selling price of the obvious, ie, between the price in cash / cash or the price of credit, from a transaction which leads to higher priced options from it, so the potential for the occurrence of usury, so it generally indicates that the law (fiqh syar´iah) Islam in terms of buy-sell